EVALUASI KUALITAS BEBERAPA GENOTIPE BAYAM (Amaranthus sp) PADA PENANAMAN DI JAWA BARAT - Suwarni Tri Rahayu; Ali Asgar; Iteu M Hidayat; Kusmana Kusmana; Diny Djuariah (BERITA BIOLOGI, 2013)
Spinach is one of leafy vegetables species that contain lots of vitamins and minerals. This study aims to examine the quality of several genotypes of spinach grown at two highland sites of West Java (Cipanas and Lembang).This experiment was conducted using Split Plot design,with five lines and five replications. Three genotype were tested, namely B1 = By16 , B2 = By18 , and B3 = By21, as well as two commercial varieties on the market spinach (B4 = red Giti , B5 = Kusuma).Measurements included physical parameters (length and width of leaves,stem diameter, texture, and color) and chemical parameters (water content, vitamin C, and fiber). The experiment was conducted in the laboratory of Physiology Vegetable Research Institute, Lembang from March to September 2012.The results showed that the content of vitamin C and fiber in genotype B1 and B2 were not significantly different from the control genotype.Similarly, the results of measurements of the length and width parameters of the leaves on all the tested genotype was not significantly different from the control genotype. Average length and width leaves of the genotype tested in Cipanas significantly higher than those tested in Lembang. Spinach has a shelf life of 1 day at room temperature in the storage area of Lembang ( 21±2°C and 85% RH ).